Tackling the tobacco epidemic in the Nordic countries and lower cancer incidence by 1/5 in a 30-year period—The effect of envisaged scenarios changing smoking prevalence. (November 2018) - Andersson, Therese M.-L.; Engholm, Gerda; Brink, Anne-Line; Pukkala, Eero; Stenbeck, Magnus; Tryggvadottir, Laufey; Weiderpass, Elisabete; Storm, Hans
Abstract: Background: Tobacco smoking is a leading cause of cancer and the most preventable cause of cancer worldwide. The aim of this study was to quantify the proportion of the cancer burden in the Nordic countries linked to tobacco smoking and estimate the potential for cancer prevention by changes in smoking prevalence. Methods: The Prevent macro-simulation model was used, estimating the future number of cancer cases in the Nordic countries over a 30-year period (2016–2045), for 13 cancer sites, under different scenarios of changing smoking prevalence, and compared to the projected number of cases if constant prevalence prevailed. Results: A total of 430, 000 cancer cases, of the 2.2 million expected for the 13 studied cancer sites, could be avoided in the Nordic countries over the 30-year period if smoking was eliminated from 2016 onwards. If prevalence of smoking is reduced to 5% by year 2030 and to 2% by 2040, 230, 000 cancer cases could be avoided. The largest proportion of cancers can be avoided in Denmark, where smoking prevalence is the highest, and similar to the prevalence in many European countries. Conclusion: A large amount of cancers could be avoided in the Nordic countries if smoking prevalence was reduced. The results from this study can be used to understand the potential impact and significance of primary prevention programmes targeted towards reducing the prevalence of tobacco smoking in the Nordic countries. Highlights: Eliminating smoking in the Nordic countries could avoid 430, 000 cancers in 30 years. The number of avoidable cases was highest for lung and bladder cancer. Lung and laryngeal cancer showed the largest percentage of avoidable cancers. Denmark had the highest number and percentage of avoidable cancers.